Application of Advance Energy Storage System in IoT and Blockchain - Ahmed Siddiqui, Fahad; Ahmed, Afshaar; Farhi, Lubna; Ahmed, Mishaal; Ahmed, Manzar; Amin, Uzma (2022)
In many under developing countries the demand of the electricity has been increased rapidly and the cost of the electricity is become very high. The researchers are focusing on cheap energy resources for sustainable future. Only few energy options are available, such as solar power and wind power systems. These systems depend on battery storage system because, if wind speed below desire limits no electricity will generated and same conditions are for solar system, if there will be no sun light or below the desire intensity of light, no electricity can be produced. The commercially available batteries are inefficient and average battery cost 500-1000 US dollars and warranty is around only two years for lead acid battery and three years for dry battery. Previously very limited research work has been done related to topic. The only solution is availability of efficient batteries with low cost and longer life span to address the present issue. Today the demand and utilization of these batteries has been increase so rapidly in many filed such as in energy sector and IoT application. One-way is to improve battery life and efficiency by using Nano coating, Nano wire and Nano batteries. In this paper, the technique presented to improve batteries and storage system for Smartgrid. Also the blockchain technique will be analyzed to control and energy transfer and charging IoT devices efficiently. For analyzing the proposed technique, the matlab simulation tool will be use.